Eliciting Frontstage and Backstage Talk with the Iterated Questioning Approach. Issue 1 (August 2016) - Robinson, Laura; Schulz, Jeremy
This article advances interviewing methods by introducing the authors' original contribution: the iterated questioning approach (IQA). This interviewing technique augments the interviewer's methodological arsenal by exploiting insights from symbolic interactionism, particularly Goffman's concepts of frontstage and backstage. IQA consists of sequenced iterations of a baseline question designed to elicit multiple forms of talk. The approach consists of four distinct steps: (1) establishing the baseline iterated question, (2) eliciting frontstage talk, (3) going backstage, and (4) eliciting backstage talk. To illuminate IQA's versatility, transcript excerpts are reproduced from interviews with two very different populations: disadvantaged high school students and business professionals. IQA promises to invigorate future interview-based inquiry by offering significant advantages compared with conventional interviewing procedures. IQA's theoretically informed question design offers a more formalized and structured approach to gather interview data on identity-relevant themes. Capitalizing on Goffman's dramaturgical framework, IQA produces readily classifiable forms of talk that correspond to frontstage and backstage self-presentations. As a result, IQA ensures replicability and allows interviewers to systematically analyze comparable talk within the same interview as well as across multiple respondents. For these reasons, IQA promises to be an innovative interviewing technique that pushes forward the methodological frontier.